Educational achievements of children aged 10-11 years with cystic fibrosis. A data linkage study in Wales - Daniela K Schlüter; Rowena Griffiths; Ashley Akbari; David Taylor-Robinson (International Journal of Population Data Science, 2022)
Introduction As people with cystic fibrosis (CF) lead longer, healthier lives, educational qualifications and employment prospects are increasingly important. However, little is known about the social consequences of CF, in particular, any impact on educational achievements and the support children with CF receive in schools.